2011
DOI: 10.1002/jssc.201100570
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of silica with a hydrophilic triol acrylamide polymer via surface‐initiated “grafting from” method for hydrophilic‐interaction chromatography

Abstract: A novel hydrophilic polymer-coated silica sorbent has been prepared using the radical "grafting from" polymerization method through surface-bound azo initiators for hydrophilic-interaction chromatography (HILIC). The azo groups were introduced to the surface of silica gel through the reaction with amino groups on the surface of silica gel with 4,4'-azobis(4-cyanopentanoic acid chloride) (ACVC). The resultant azo-immobilized silica gel served as surface initiator to polymerize hydrophilic triol acrylamide monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 39 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…This TRIS acrylamide grafted silica gel showed different selectivity, substantially higher retention capacity and reduced weak anion exchange properties compared to those of the TRIS amine silica stationary phase. In addition, a similar TRIS acrylamide functionalized silica stationary phase has been prepared using a different approach via azo immobilized silica gel . The resulting poly N ‐acryloyl‐TRIS stationary phase showed a mixed mode retention mechanism of hydrophilic and ionic interactions due to the residual amine groups originating from the amino propyl silica used at the starting material of the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This TRIS acrylamide grafted silica gel showed different selectivity, substantially higher retention capacity and reduced weak anion exchange properties compared to those of the TRIS amine silica stationary phase. In addition, a similar TRIS acrylamide functionalized silica stationary phase has been prepared using a different approach via azo immobilized silica gel . The resulting poly N ‐acryloyl‐TRIS stationary phase showed a mixed mode retention mechanism of hydrophilic and ionic interactions due to the residual amine groups originating from the amino propyl silica used at the starting material of the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for the analysis of polar and highly hydrophilic analytes in biological and environmental samples has promoted the development of HILIC, especially HILIC stationary phases . Aside from various newly developed silica‐based polar packing materials, there are some commercially specially designed columns for HILIC separation, such as TSKgel amide‐80, zwitterionic (ZIC)‐HILIC and Atlantis HILIC silica .…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal of his syntheses was to develop highly hydrophilic phases for ion‐exchange chromatography of proteins, and until very recently the use of TRIS‐acrylamide modified silica has not been tested in HILIC. A few months ago Peng et al published a work where they had synthesized a grafted polymeric silica phase with TRIS‐acrylamide from surface‐bound azo initiators and tested it for HILIC separation of nucleoside and peptides . It was concluded that this phase expressed both hydrophilic interaction and a WAX‐type ion exchange retention pattern, the latter attributed to residual amino groups originating from the aminopropylated silica used as starting point in the synthesis.…”
Section: Introductionmentioning
confidence: 99%